Anti-Microbial Effect Of Different Time’sexposureofozonized Gas And Ozonized Water Onperiodontalpathogens (In Vitro Study) - Ahmmad, Ban Z; Ibraheem, Leqaa M (Journal of Baghdad College of Dentistry, 2017)
Background: the oral cavity is consider to be an open ecosystem, with the balance between the microorganism’s entrance and the defenses of the host. The initiation of periodontitis has been associated with restricted kinds of anaerobic bacteria, such as Aggregatibacter actinomycetemcomitans (A.a) and Porphyromonas gingivalis (P.g) in plaque subgingivally. Ozone has a biological effects on bacteria due to oxidation of bio-molecules and its toxins. The aim is to determine and compare the antimicrobial effect of gaseous ozone and ozonized water on the growth of isolated anaerobic bacteria (A.a and P.g) when exposed to different time intervals.Materials and methods:This experiment is done byozone generator OLYMPIC- III(600mg/hr) to generator the gaseous ozone (218ppm/W-air)which bypassed around the agar plates containing on of the isolated bacteria with different time intervals (1-10 minutes).And with special aeration stone for generation of ozonized water (0.6 ppm) with different time intervals (1-15 minutes).Results: Gaseousozone have a significant reduction in the bacterial growth on the agar plates for (A.a) was 7 minutes and (P.g) was 4 minutes. While ozonated water have also a significant reduction in the bacterial growth on the agar plates for (A.a) was 5 minutes and (P.g) was 4 minutes. Conclusion: Bothgaseousozone and ozonized water are a powerful antimicrobialeffects on anaerobic microorganism isolated from chronic periodontitis patients.